(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Social media advertising has become a critical tool for brand building, particularly in emerging markets, where digital adoption is rapidly expanding. This study explores the impact of social media advertising on brand equity, focusing on how platforms such as Facebook, Instagram, Twitter, LinkedIn, and YouTube influence consumer perception, brand awareness, trust, and loyalty. By analysing various advertising strategies, including influencer marketing, targeted ads, and user-generated content, the research aims to determine how social media contributes to brand differentiation and competitive advantage. Additionally, it examines the challenges businesses face, such as misinformation, data privacy concerns, and consumer skepticism, which can affect brand credibility. Using a combination of quantitative and qualitative research methods, the study evaluates consumer responses to social media advertising and its effectiveness in shaping brand equity. The findings provide valuable insights for businesses, digital marketers, and policymakers, helping them develop more effective social media marketing strategies. This research highlights the growing significance of digital advertising in emerging markets, offering practical recommendations for brands to enhance their market presence, customer engagement, and long-term brand value.